Menumbuhkan Pendidikan Karakter melalui Lingkungan Kerja yang Tercipta bagi Aparatur Sipil Negara: Nurturing Character Education through an established Working Environment for Government Employees - Devi Irena; Dasim Budimansyah (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2022)
Character education is currently being promoted in various educational institutions. Various methods have been undertaken, one of which is using the work environment. With this method, the character development of learners can be established and monitored directly. Starting from this condition, this research was conducted to describe the implementation of character building through the work environment and the impact of the emerging values of character building through the work system conducted at the Institute of Education of Institute Government of Home Affairs (IPDN). This research is grounded in three coding systems, where sampling was conducted purposively. Technical analysis of the data consisted of data reduction, data presentation and conclusion. The findings revealed that an educational process comprised of character values in a work environment could help to improve work behaviors.